Costo de capital y rentabilidad en empresas de transporte terrestre de pasajeros - Ramírez Huerta, Valiente Pantaleón (2018)
Objective: To determine the incidence of the weighted average cost of capital in the profitability of the companies of interprovincial transport of passengers by road in buses in a five-year period 2012 - 2016. Methods: Applied research and a correlational design, the population was of 428 companies and the sample 38; the data was obtained through a survey questionnaire applied to officials of the aforementioned companies. Results: In the above-mentioned five-year period the companies under study show a capital structure composed of direct credit and banking of 15.32% at a cost of 9.97% per annum, and the percentage per financial lease was 41.34% at a cost of 8.70% annually. Additionally, by own capital the percentage was 43.34% at a cost of 15.15% per annum. Therefore, the weighted average cost of capital resulted on 11.80% per annum. In terms of profitability, the return on the asset was 9.61% per annum, a return on net equity, 3.29% per annum and a return on sales of 2.24% per annum. According to Pearson's correlation index, the weighted average cost of capital is not correlated with the return on assets, net equity nor sales. Conclusions: According to the hypothesis test, neither the weighted average cost of capital nor its components are correlated with the return on the asset, only the weighted average cost of debt financing is inversely correlated with the return on net equity and on sales.